2018
DOI: 10.1016/j.mbs.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Models in neuroendocrinology

Abstract: The neuroendocrine systems of the hypothalamus are critical for survival and reproduction, and are highly conserved throughout vertebrate evolution. Their roles in controlling body metabolism, growth and body composition, stress, electrolyte balance and reproduction have been intensively studied, and have yielded a rich crop of original and challenging insights into neuronal function, insights that circumscribe a vision of the brain that is quite different from conventional views. Despite the diverse physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 162 publications
(154 reference statements)
0
12
0
Order By: Relevance
“…Some of these benefits have been already described in several reviews. The review in [1] covers general principles of modelling in neuroendocrinology using the growth hormone system as an example, while a recent review by the same authors addresses the contributions of modelling to hypothalamic–pituitary neurosecretory systems [2]. The review in [3] describes in detail several mathematical modelling tools such as types of equations, analysis of their dynamic behaviour (e.g., bistability , oscillations), and approaches to deal with biological noise and systems with multiple timescales in view of applications in endocrinology.…”
Section: Understanding the Complexity Of Endocrine Regulation Demandsmentioning
confidence: 99%
“…Some of these benefits have been already described in several reviews. The review in [1] covers general principles of modelling in neuroendocrinology using the growth hormone system as an example, while a recent review by the same authors addresses the contributions of modelling to hypothalamic–pituitary neurosecretory systems [2]. The review in [3] describes in detail several mathematical modelling tools such as types of equations, analysis of their dynamic behaviour (e.g., bistability , oscillations), and approaches to deal with biological noise and systems with multiple timescales in view of applications in endocrinology.…”
Section: Understanding the Complexity Of Endocrine Regulation Demandsmentioning
confidence: 99%
“…6L ), confirming that they were indeed action potentials. Moreover, we found that in magnocellular (non-CRH) neuroendocrine neurons of the PVN, which are known to have ex vivo intrinsic properties (Luther et al, 2002) and in vivo firing patterns (Leng and MacGregor, 2018) different from CRH PVN neurons, the identical network current failed to trigger the RB ( Fig. 6M, N ).…”
Section: Resultsmentioning
confidence: 89%
“…We refer the reader to a former review (Yvinec et al, 2018) for other interesting biomathematical issues raised by the HPG, such as (i) the detection and possible reconstruction of pulsatile secretion events, and (ii) the modeling of hormonal blood levels in males or females (ovarian cycle). We also mention recent reviews dealing with related topics: mathematical neuroendocrinology (Bertram, 2015;Leng and MacGregor, 2018), electrophysiology in pituitary cells (Fletcher et al, 2018), and general modeling issues in endocrine systems (Zavala et al, 2019).…”
Section: Biological Background and Review Scopementioning
confidence: 99%
“…As such, they undergo a process of excitation-secretion coupling underlain by electrophysiological steps. There is a huge literature in electrophysiological modeling, amongst which numerous studies have been dedicated to either GnRH neurons or gonadotrophs (most of them are reviewed in (Bertram, 2015), (Fletcher et al, 2018) or (Leng and MacGregor, 2018)). We will just pick-up some instances that can give a flavor of more comprehensive descriptions.…”
Section: Electrophysiological Models For Gnrh Neurons and Gonadotrophsmentioning
confidence: 99%